Assessment of stressful life events for patients with substance abuse in Baghdad city - Shakhat, ali; hashim, Mushatq (Iraqi National Journal of Nursing Specialties, 2013)
Objective: The present study aims to assess the stressful life events for patients with substance abuse in Baghdad city.Methodology: A descriptive study was carried out at (Baghdad teaching hospital and Ibn-Rushed Psychiatric hospital).Starting from 1st of December 2012 to 3rd of July 2013, A non-probability (purposive) sample of 64 patients thatdiagnosed with substance abuse, the data were collected through the use of semi-structured interview byquestionnaire, which consists of three parts sociodemographic data, medical information, and Life events scaleconsists of 49-items distributed to six domains including, family and social domain, health domain, security, legal andcriminal domain, work and school domain, financial domain, and change of residence domain. A pilot study wascarried out to determine the questionnaire reliability through the use of (Cronbach alpha). Validity of the instrumentwas established through penal of (13) experts. Data was analyzed by application of descriptive and inferentialstatistical methods.Results: The study findings revealed that all sample (100%) are males, and about half of sample were at age (20-29)years, (50.8%) of them had completed primary school, married, unskilled worker, and more than two third- of themwere living in urban area. Health domain and family and social domain had more effects on patients than otherdomains.Recommendations: Increase the individual awareness about management of the stressful life events to decrease theimpact of life events upon their Psychological health